The Trichotomy of Islam, Democracy, and Secularism in Indonesia Post The Conservative Turn - Moch. Muwaffiqillah (Tribakti: Jurnal Pemikiran Keislaman, 2023)
This article examines the arguments for accepting democracy from an Islamic perspective after the conservative turn in Indonesia. The idea of democracy in the Islamic context revolves around several mainstream arguments as theological and sociological justifications. On the other hand, the Muslim community tends to be opposed and allergic to the concept of secularization, which in some ways, is a mandatory requirement for the establishment of a strong democracy. Though some Islamic scholars argue that Islam and democracy are compatible, the role of secularism is important to be emphasized. This research is a descriptive qualitative method included in the library research category. The qualitative description method is used because of its suitability to the topic and focus of the study. This research shows that recent developments in Muslim acceptance of democracy that does not require secularism in Indonesia after the conservative turn provide proof that the tracheotomy can be united. Furthermore, several political events in Indonesia have revealed how both Islamic political parties and Islamic intellectuals have contributed to the development of liberal democracy. So this study implies that whereas Islam, democracy and secularism were originally considered a trichotomy that cannot be harmonized, the political results in Indonesia have disproved it. In particular, the dynamics of Islamic political development in Indonesia decades after the conservative turn shows that liberal democracy will reach peak development in the coming years.